(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we propose a multi-stage HIV infection model with general incidence rate to describe the influence of raltegravir intensification on viral dynamics. The basic reproduction number R_0 is established. The infection-free equilibrium E_0 is locally asymptotically stable if R_0 1.